Pollen morphology of four species of Jatropha (Euphorbiaceae), including toxic varieties, in Northwestern Mexico - Soto-Landeros, Federico (2017)
Jatropha curcas is a native Mexican plant, distributed in the forests of coastal regions; it has shown potential for the production of biofuel, and its raw protein can be used as animal feed. Nevertheless, its current varieties have low yield and production variability, as it is in domestication period. The knowledge of the pollen grains is fundamental for studies of Jatropha reproductive biology and breeding for genetic improvement to generate new hybrids and improve fruit and seed yield. This study compared pollen morphology of four Jatropha species, which include two varieties of J. curcas (one toxic from India and one non-toxic from Mexico), and two varieties of wild J. cinerea (Sinaloa and Baja California Sur); additionally, pollen was collected from wild J. platyphylla (Sinaloa) and J. vernicosa (Baja California Sur) to characterize them palynologically. We used a scanning electron microscope to describe the size and shape of pollen grains. Pollen grains were observed spheroidal. The diameter of the varieties of toxic and non-toxic J. curcas and that of J. platyphylla were 58 ± 2.3, 54 ± 1.7, and 51 ± 2.4 µm, respectively; the number of clavae was 84 ± 10, 108 ± 15, and 180 ± 15.5, respectively. Pollen grains of J. cinerea (Sinaloa) had a diameter of 50 ± 1.7 µm and 220 ± 14 clavae by area; J. cinerea (Baja California Sur) had a diameter of 45 ± 1.9 µm and 195 ± 14.7 clavae. Pollen grains of J. vernicosa had a diameter of 46 ± 2.1 µm and 231 ± 25.6 clavae. The ornamentation of the exine showed clava with capita gemma shaped for varieties of J. curcas species and clavum shaped for J. platyphylla, J. cinerea and J. vernicosa species. The studied varieties have a cross-linked endexine and ectexine intectate. Luminal bacules were observed in the reticular space of J. curcas varieties while none were present in the varieties of J. cinerea, J. platyphylla, and J. vernicosa.